Data-Based Participatory Facilities and Infrastructure Management Model for Improving the Quality of Basic Education in the Archipelago - Rahmat Saleh, Rahmat Saleh; Hizir, Hizir; Niswanto, Niswanto; Salfiadis, Salfiadis (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
​Objective: This study aims to develop a participatory and data-based model for managing basic education facilities and infrastructure to improve the quality of education services in the archipelago. The focus of the research is directed at the optimization strategy of BOS funds, the implementation of School-Based Management (SBM), and the use of data-based School Facilities Management System (SFMS). Methods: This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observations, and documentation studies. The research informants consisted of principals, teachers, and committees in two elementary schools in Simeulue Regency, who were purposively selected. Data analysis was carried out through reduction, thematic presentation, and conclusion drawing, with triangulation validation of sources and methods. Results: The results of the study show that the planning and implementation of infrastructure management have been carried out in a participatory, adaptive, and data-based manner, with school principals playing a central role in coordination. The main challenges include limited BOS funds, technical personnel and digital literacy. From the field findings, an Integrative Model for Participatory Facilities and Infrastructure Management (ISPBD Model) was formed, which emphasizes collaboration, budget efficiency, and public accountability. Novelty: This research offers a new conceptual model that integrates the principles of SBM, BOS fund optimization, and data-driven facility management, which has not previously been developed in an integrated manner in the context of elementary schools in the Indonesian archipelago.​